2010
DOI: 10.1002/cyto.a.20927
|View full text |Cite
|
Sign up to set email alerts
|

Detection of TiO2 nanoparticles in cells by flow cytometry

Abstract: Evaluation of the potential hazard of man-made nanomaterials has been hampered by a limited ability to observe and measure nanoparticles in cells. In this study, different concentrations of TiO 2 nanoparticles were suspended in cell culture medium. The suspension was then sonicated and characterized by dynamic light scattering and microscopy. Cultured human-derived retinal pigment epithelial cells (ARPE-19) were incubated with TiO 2 nanoparticles at 0, 0.1, 0.3, 1, 3, 10, and 30 lg/ml for 24 hours. Cellular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
214
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(224 citation statements)
references
References 49 publications
6
214
3
1
Order By: Relevance
“…These techniques require a fluorescence signal from the NPs which can derive from an intrinsic property of NPs exhibiting the capacity to emit the light, for examplesemiconductor nanocrystals such as quantum dots [15] and titanium dioxide NPs [16] or by the use of fluorescence tags [17]. These types of NPs can be detected and quantified by fluorescence spectroscopy, flow cytometry, or fluorescence imaging techniques.…”
Section: Np Quantification Techniques: Some Illustrative Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques require a fluorescence signal from the NPs which can derive from an intrinsic property of NPs exhibiting the capacity to emit the light, for examplesemiconductor nanocrystals such as quantum dots [15] and titanium dioxide NPs [16] or by the use of fluorescence tags [17]. These types of NPs can be detected and quantified by fluorescence spectroscopy, flow cytometry, or fluorescence imaging techniques.…”
Section: Np Quantification Techniques: Some Illustrative Examplesmentioning
confidence: 99%
“…Forward scattered light is useful to determine the volume of the cell, thus the reference volume is defined in this specific technique. It is a fast method to obtain the relative amount of cells loaded and/or associated with fluorescently labeled NPs (or possessing fluorescent properties) [16,17]. In addition, the cells have to be labeled in order to define the reference volume.…”
Section: Np Quantification Techniques: Some Illustrative Examplesmentioning
confidence: 99%
“…It was demonstrated that TiO 2 78, 79, 80 and Ag81 NMs induce an increase of SS signal in cell populations after exposure to both NMs. SS indicates the granularity of the cells and is strongly linked to their content of NMs.…”
Section: High‐throughput Flow Cytometrymentioning
confidence: 99%
“…SS indicates the granularity of the cells and is strongly linked to their content of NMs. As few as 5–10 NMs per cell can be detected 79. Recently, SS signal analysis was successfully applied for detecting carboxylated nanodiamonds and tungsten carbide‐cobalt (WC‐Co) NMs in cells, results being validated by Raman and confocal microscopy associated with 3D reconstruction 82, 83.…”
Section: High‐throughput Flow Cytometrymentioning
confidence: 99%
“…15 Compared to the conventional cell based assays measuring cellular responses collectively, the cytometric approach measuring individual cellular information seems to have huge potential as an alternative assay protocols that can circumvent or overcome various limitations of nanotoxicity assessments. For instance, recent flow cytometry studies by Zucker et al 16 have provided useful insight into the detection of cellular NP associations and resultant toxicities, while Suzuki et al 17 have proposed scattering-based flow cytometry as a simple and easy method to evaluate cellular association of NPs that can be used as a cost-effective technique for initial screening of the nanotoxicity. Thus, we believe that the image cytometry based MTT cell viability assay protocols proposed in this study also provided a simple, reliable, and unbiased method to evaluate nanotoxicity of TiO 2 NPs and can be further modified and expanded for the cytotoxicity assessment of various manufactured nanomaterials.…”
Section: P25mentioning
confidence: 99%